2018
DOI: 10.3389/fmicb.2018.01530
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Phenotypic Antibiotic Susceptibility Testing of Uropathogens Using Optical Signal Analysis on the Nanowell Slide

Abstract: Achieving fast antimicrobial susceptibility results is a primary goal in the fight against antimicrobial resistance. Standard antibiotic susceptibility testing (AST) takes, however, at least a day from patient sample to susceptibility profile. Here, we developed and clinically validated a rapid phenotypic AST based on a miniaturized nanotiter plate, the nanowell slide, that holds 672 wells in a 500 nl format for bacterial cultivation. The multitude of nanowells allows multiplexing with a panel of six antibioti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Bacterial strains used in this study are listed in Supplementary Table S1. Clinical UPEC strains used in biofilm tests have been published (Veses-Garcia et al, 2018). Mutants were prepared in E. coli CFT073 using the λ-red recombination system (Datsenko and Wanner, 2000;Yu et al, 2000).…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bacterial strains used in this study are listed in Supplementary Table S1. Clinical UPEC strains used in biofilm tests have been published (Veses-Garcia et al, 2018). Mutants were prepared in E. coli CFT073 using the λ-red recombination system (Datsenko and Wanner, 2000;Yu et al, 2000).…”
Section: Bacterial Strains and Growth Conditionsmentioning
confidence: 99%
“…To study whether the observed changes in colony biofilm in response to nitrate was common among UPEC strains, we evaluated the colony biofilm morphotypes in a collection of 40 clinical UPEC isolates (Veses-Garcia et al, 2018). A palette of strain dependent phenotypes was seen when grown on CR LBNS agar in the absence or presence of 20 mM nitrate, with 22 of 40 demonstrating a decrease in CR binding and/ or colony roughness (Supplementary Figure S1).…”
Section: E Coli Cft073 Biofilm Morphotypes Are Modulated By Membranementioning
confidence: 99%
“…A basic approach to understanding the mechanism of antibiotics is to observe the phenotypic or physical response of bacteria to antibiotics. Phenotypic imaging has been one of the most popular diagnostic methods to achieve rapid antimicrobial susceptibility testing [5][6][7][8][9][10], as it provides an easy, low cost, real-time single-cell level examination. Furthermore, phenotypic analysis of bacteria has been exploited to extract useful information in various fields such as epidemiology and systems biology [11].…”
Section: Introductionmentioning
confidence: 99%
“…In nanowell AST, morphotyping with a phase contrast microscopy and optical signal analysis is performed for 0.5 μl cultures. Antibiotic susceptibility data can be obtained for uropathogens in <4 h. The system showed a total categorical agreement of 97.9% with standard disk diffusion assays, but a careful standardization of cell densities prior to cultivation was found necessary (Veses-Garcia et al, 2018 ).…”
Section: Proof-of-concept Technologiesmentioning
confidence: 99%
“…They were able to define a precise minimum inhibitory concentration for 70 clinical E. coli isolates. Algorithm-assisted optical analysis determined antibiotic susceptibility in 3 h 40 min, showing a total categorical agreement of 97.9% (Veses-Garcia et al, 2018 ).…”
Section: Miniaturized and Chip-based Growth Monitoring Systemsmentioning
confidence: 99%